Flowering and rhizomes qualities of Curcuma hybrid (C. petiolata Wall, × C. aurantiaca van Zijp) affected by NPK - Ruamrungsri S. (2014)
Effect of NPK levels in nutrient solution were studied in Curcuma hybrid (C. petiolata Wall. × C. aurantiaca Van Zijp) growing in substrate culture. The media consisted of sand and rice-husk charcoal at the ratio 1:1 (v/v). Three levels of nitrogen (100, 200 and 300 mg N L-1) combined with two levels of phosphorus (50 and 100 mg P L-1) and two levels of potassium (200 and 300 mg K L-1) were supplied to plants twice a week from planting to flowering (18 wk after planting) and changed the rate to once a week from flowering until one month before harvest (22 wk after planting). The results showed that the combination of 200 mg N L-1 and 50 mg P L-1 promoted plant growth and flower qualities in terms of plant height, spike length, spike width and length of flower stalk. Potassium concentration at 200 and 300 mg L-1 did not give different results in all parameters. Increment of nitrogen concentration up to 300 mg L -1 increased number of rhizomes but decreased length of storage roots. The interaction effect of N × P affected nitrogen content in the leaves while the other effects were not significantly different. The combination of N:P:K at 200:50:200 mg L-1 could be used for substrate production of this plant.